Body size and age estimation of Chinese sea bass (Lateolabrax maculatus) and evidence of Late Neolithic fishing strategies, a case study from the Guye site - Yu, Chong; Cui, Yong (Frontiers in Ecology and Evolution, 2022)
Fishing has been an important form of subsistence economy among ancient societies. However, details of past fishing activities have been rarely studied in China. This paper uses data extracted from modern fish collection to estimate the body size and age of Chinese sea bass from the Guye site, a common species that frequently discovered in archaeological sites of coastal south China. The distribution of body size and age were reconstructed, combining with fish biology and ecology, current dataset revealed that the main fishing ground of the Late Neolithic Guye people is close to the shoreline, and the main fishing seasons is from spring to early autumn.